2018
DOI: 10.4149/neo_2018_170724n498
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA DANCR facilitates glioma malignancy by sponging miR-33a-5p

Abstract: Glioma is among the most fatal brain tumors characterized by a highly malignancy and rapid progression and early metastasis. Dysregulation of long non-coding RNA differentiation antagonizing non-protein coding RNA (LncRNA DANCR) is associated with the development, progression and metastasis of various cancers. In the present study, we investigated functional role of LncRNA DANCR in the malignancy of glioma. The results showed that LncRNA DANCR was increased in glioma tissues and cells compared with normal brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 24 publications
(31 reference statements)
2
28
0
Order By: Relevance
“…One critical mechanism by which lncRNAs regulate gene expression is acting as ceRNAs to sponge targeted miRNAs (Salmena et al, 2011). This is also true for DANCR, not only because several miRNAs have been identified as direct targets of DANCR, but also the function of DANCR is prominently mediated through downregulating the expression of these miRNAs, as reported by recent studies Lu et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Xu et al, 2018;Yang et al, 2018), to name a few. Combining predictive methods and some biochemical experiments, we demonstrate that miR-874-3P is a new binding target of DANCR and that by suppressing the inhibitory effect of miR-874-3P on ATG16L1 expression via interacting and decreasing miR-874-3P level, DANCR possesses an ability to upregulate ATG16L1 expression.…”
Section: Disscussionmentioning
confidence: 89%
“…One critical mechanism by which lncRNAs regulate gene expression is acting as ceRNAs to sponge targeted miRNAs (Salmena et al, 2011). This is also true for DANCR, not only because several miRNAs have been identified as direct targets of DANCR, but also the function of DANCR is prominently mediated through downregulating the expression of these miRNAs, as reported by recent studies Lu et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Xu et al, 2018;Yang et al, 2018), to name a few. Combining predictive methods and some biochemical experiments, we demonstrate that miR-874-3P is a new binding target of DANCR and that by suppressing the inhibitory effect of miR-874-3P on ATG16L1 expression via interacting and decreasing miR-874-3P level, DANCR possesses an ability to upregulate ATG16L1 expression.…”
Section: Disscussionmentioning
confidence: 89%
“…Furthermore, Guo et al reported that lncRNA SNHG20 promotes cell proliferation and invasion by the miR‐140‐5p‐ADAM10 axis in cervical cancer. Recently, many studies have reported that lnc‐DANCR plays an important role in esophageal cancer, glioma, osteosarcoma, colorectal cancer, cervical cancer, and so on. Recently, Liang et al reported that lnc‐DANCR promoted cervical cancer progression by upregulating ROCK1 through sponging miR‐335‐5p .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, DANCR regulated RAB1A expression in glioma by functioning as a ceRNA of miR-634 [27]. In addition, DANCR has been reported to promote glioma malignancy by miR-33a-5p [28]. However, there are no more reports on target miRNAs of DANCR in glioma.…”
Section: Discussionmentioning
confidence: 99%